Dynein-mediated Vesicle Transport Controls Intracellular Salmonella Replication - Marsman, Marije (The American Society for Cell Biology, 2004)
Salmonella typhimurium survives and replicates intracellular in a membrane-bound compartment, the Salmonella-containing vacuole (SCV). In HeLa cells, the SCV matures through interactions with the endocytic pathway, but Salmonella avoids fusion with mature lysosomes. The exact mechanism of the inhibition of phagolysosomal fusion is not understood. Rab GTPases control several proteins involved in membrane fusion and vesicular transport. The small GTPase Rab7 regulates the transport of and fusion between late endosomes and lysosomes and associates with the SCV. We show that the Rab7 GTPase cycle is not affected on the SCV. We then manipulated a pathway downstream of the small GTPase Rab7 in HeLa cells infected with Salmonella. Expression of the Rab7 effector RILP induces recruitment of the dynein/dynactin motor complex to the SCV. Subsequently, SCV fuse with lysosomes. As a result, the intracellular replication of Salmonella is inhibited. Activation of dynein-mediated vesicle transport can thus control intracellular survival of Salmonella.